Promoting Positive Behavior Using the Good Behavior Game: A Meta-Analysis of Single-Case Research. (July 2016) - Bowman-Perrott, Lisa; Burke, Mack D.; Zaini, Samar; Zhang, Nan; Vannest, Kimberly
The Good Behavior Game (GBG) is a classroom management strategy that uses an interdependent group-oriented contingency to promote prosocial behavior and decrease problem behavior. This meta-analysis synthesized single-case research (SCR) on the GBG across 21 studies, representing 1, 580 students in pre-kindergarten through Grade 12. The TauU effect size across 137 phase contrasts was .82 with a confidence interval 95% CI = [0.78, 0.87], indicating a substantial reduction in problem behavior and an increase in prosocial behavior for participating students. Five potential moderators were examined: emotional and behavioral disorder (EBD) risk status, reinforcement frequency, target behaviors, GBG format, and grade level. Findings suggest that the GBG is most effective in reducing disruptive and off-task behaviors, and that students with or at risk for EBD benefit most from the intervention. Implications for research and practice are discussed.